Religion og kultur hos Harald Høffding - Foss, Poul Juul (Kirkehistoriske Samlinger, 1996)
Harald Høffding (1843 - 1931), professor of philosophy at the University of Copenhagen 1883 - 1915 was an internationally aknowledged scholar of his time. He was eclectic in his way of thinking, although he approached possitivism and utilitarism. But religious problem was an issue that interested Høffding. He treated the religious problems from a psychological point of view, but the ethical and cultural aspects of them were his main concern. Could religion have a positive impact on people in society, make them active and harmonious, he asked. In this article I will look upon Høffding’s thoughts from a theological point of view, theology being in fact one of Høffding’s foundations (cand.theol. 1865). My thesis is, that Høffding was in a conflict with Christianity which, in his opinion, probably wouldn’t survive as anything else but an ethic, cosmic-poetic attitude towards life far from its historic source.